Relationship Between Home Care Service Quality and Independence of Stroke Patients - Setia, Glaudina; Wahab, Wahyuni; Alam, Muh Syahrul; Anto, Ambo (Omni Health Journal, 2026)
Background: Stroke is a medical condition caused by disruption of blood flow to the brain, leading to cell death and often resulting in paralysis. This condition can reduce patients’ confidence and independence, particularly among individuals in the productive age group. Objective: This study aimed to determine the relationship between service quality and the independence of stroke patients. Methods: This study employed a quantitative approach with an analytical cross-sectional design. The sample consisted of 40 stroke patients receiving home care services. Data were collected using structured questionnaires and analyzed using the Chi-square test. Results: The findings indicated a significant relationship between service quality and patient independence. Patients who received better-quality services tended to have higher levels of independence. Statistical analysis showed a p-value of 0.000 (< 0.05), confirming the significance of the relationship. Conclusion: There is a significant relationship between home care service quality and the independence of stroke patients. Improving service quality is essential to enhance patient independence in home care settings.